Analisis Wacana Terkait Percakapan Konsep Matematika - Herna Herna (Fakultas Keguruan dan Ilmu Pendidikan Univ. Al Asyariah Mandar Sulbar, 2018)
This article offers discourse analysis to facilitate interpretation of discourse content presented in map form. This is intended to mean the content of discourse is not messy. Discourse analysis includes, selecting transcripts, creating lexical chain tables, constructing a